Physicochemical Properties of Rapeseed Cake and its Potential as a Biomass Reductant of Metallurgical Slags - Ł. Myćka; J. Łabaj; P. Madej; Ł. Kortyka; P. Palimąka; T. Matuła; A. Bukowska (Archives of Foundry Engineering, 2025)
The paper presents the results of a study of the basic physical and chemical properties of a reductant traditionally used in the metallurgical industry, i.e. coke, and an alternative biomass reductant, rapeseed cake. The article also presents the results of research into the reduction of smelter slag with a high content of Cu and Pb with rapeseed cake and, for reference purposes, coke. The tests were conducted at 1400 oC and a holding time, 2h. The reductant additions ranged from 2-20 % by weight of the charge (slag) for biomass and 5, 10 and 15 for coke. The results obtained are discussed in the context of several parameters to assess the efficiency of the reduction processes.